Analysis of persistent organochlorine pesticides in shellfish and their risk assessment from aquafarms in Taiwan. (November 2021) - Wang, Jiann-Hsiung; Chang, Chung-Pei; Chang, Chia-Chia; Wang, Chao-Min; Lin, Chuen-Fu; Lin, Jen-Wei; Lin, Wei-Li; Liao, Huei-Jyuan; Kao, Chen-Yung; Fan, Pei-Shan; Yang, Wei-Cheng; Chang, Geng-Ruei
Abstract: In Taiwan, freshwater clams ( Corbicula fluminea ) and hard clams ( Meretrix lusoria ) are the most frequently raised shellfish in land-based pond aquaculture, but research on the accumulation of organochlorine pesticides (OCPs) in these shellfish is limited. We detected the levels of 14 OCPs in 62 shellfish from Taiwanese aquafarms by performing gas chromatography–tandem mass spectrometry. OCP residues were detected in 4.84% of the samples including readings of 0.04 mg/kg chlordane (in a freshwater clam), 0.03 mg/g p, p ′-DDE (in a freshwater clam), and 0.02 mg/g p, p ′-DDE (in a hard clam). However, the associated estimated daily intake values were less than the acceptable daily intake levels of chlordane and p, p ′-DDE Therefore, the consumption of these shellfish presents no immediate health risks. Our findings contribute to food safety and serve as a reference for OCP screenings for aquatic shellfish. Highlights: Organochlorine pesticides residues were detected in 62 shellfishes by using GC–MS/MS. Samples contained chlordane residues at 0.04 mg/kg, and p, p ′-DDE at 0.02–0.03 mg/g. For Taiwanese men and women, the EDI is less than 0.1% of the ADI for OCP residues. Collectively, no immediate health risk for shellfish consumption in Taiwan